Innovation in the teaching of statistics (Revista Electrónica Diálogos Educativos. REDE, 2017)
The present document reports an innovative intervention of the teaching practice in the field of statistics with the university students of education in Guanajuato University. The purpose was to promote meaningful learning, operationalized in a qualitative level, through didactic strategies that help in certain levels of achievement, based on the use of a critical path of learning. We used a qualitative research-action methodology, supported by other methodologies such as ethnography and phenomenology, through the use of the records of observation of three sessions: the first corresponded to the situation of the students in a critical path and the two other sessions were devoted to carry out the innovation. The results reveal an increase in the level of achievement of the majority of the students and in the transference of learning, the students being more reflective.